2019
DOI: 10.3892/or.2019.7304
|View full text |Cite
|
Sign up to set email alerts
|

High blood levels of soluble OX40 (CD134), an immune costimulatory molecule, indicate reduced survival in patients with advanced colorectal cancer

Abstract: The interaction between tumor necrosis factor receptor superfamily, member 4 (OX40) on T cells and the OX40 ligand (OX40L) on antigen-presenting cells (APCs) is a pivotal step for T-cell activation and the promotion of antitumor immunity. However, it is hypothesized that soluble OX40 (sOX40) in blood suppresses T-cell activation by blocking the OX40/OX40L interaction. In the present study, the association between blood sOX40 levels and the clinical characteristics of advanced colorectal cancer (CRC) patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…A few studies have been conducted on the serum levels of OX40 in different malignancies. Adult patients of T-cell leukemia demonstrated elevated serum OX40 levels while Sawada et al reported an association between higher serum levels of OX40 and reduced survival time in advanced stage colorectal patients (n=22) [ 12 - 13 ]. Similarly, Kashima et al in advanced lung adenocarcinoma (n=56) reported higher levels were associated with poor prognosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have been conducted on the serum levels of OX40 in different malignancies. Adult patients of T-cell leukemia demonstrated elevated serum OX40 levels while Sawada et al reported an association between higher serum levels of OX40 and reduced survival time in advanced stage colorectal patients (n=22) [ 12 - 13 ]. Similarly, Kashima et al in advanced lung adenocarcinoma (n=56) reported higher levels were associated with poor prognosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 16 OX40 is expressed frequently in breast cancer, melanoma, head and neck cancer, colon cancer, and B cell lymphoma cells. [17][18][19] The signals from the binding of OX40 and its ligand promote effector T-cell expansion and survival by enhancing the expression of cyclin A, cyclin-dependent kinases, Bcl-2 antiapoptotic molecules, multiple cytokines and related receptors like interleukin (IL)-2. 20 In addition, OX40 signaling promotes the generation of memory T cells and inhibits the function of Tregs.…”
Section: Ox40mentioning
confidence: 99%
“…It was demonstrated that the combination of CXCL12 with CXCR4 and CXCR7 on tumor cells leads to antiapoptotic signals upregulated by Bcl‐2 and survivin, and affects the progression of gastrointestinal tumors 34 . The soluble TNFSF4 in the blood is positively correlated with carbohydrate antigen (CA) 19‐9, carcinoembryonic antigen, C‐reactive protein, and soluble programmed cell death ligand‐1 in patients with CRC 35 . These results indicate a strong correlation between Syk and immune features.…”
Section: Discussionmentioning
confidence: 98%